The Research Needs on Social Aspects of Biochar: A Learning from Social-Economy of Biochar Previous Study - Purnomo, Agustina Multi (Universitas Djuanda, 2025)
Biochar has been extensively studied in terms of technical and environmental aspects. The study of social aspects of biochar was infrequent. Research on the social aspects of biochar was more often linked with technological, environmental, or economic aspects. This study utilized initial data from socioeconomic aspects because socioeconomic research was more prevalent than socio-technical or socio-environmental research. The study employed a third-step analysis analysis. First, a bibliometric analysis was conducted to examine research topics related to the social economy of biochar from published articles in Scopus and Google Scholar. Data processing was used VOSviewer and the keyword